The Influence of Electronic Word of Mouth (E-WOM), Celebrity Endorsers, and Country of Origin on Purchasing Decisions for Skintific Products - Felik Sad Windu Wisnu Broto; Erica Adriana; Aquina Tiara Dewi (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study was to analyze and determine the effect of electronic word of mouth (e-wom), celebrity endorsers, and country of origin on purchasing decisions for Skintific products. This study uses a quantitative method approach. The population used is the Indonesian people who use or have used Skintific products with a sampling of 272 respondents. The sampling technique used is non- probability sampling with purposive sampling method. The results show that e-wom, and country of origin have a positive and significant influence on purchasing decisions, while celebrity endorsers have a negative influence on purchasing decisions. The results of this study suggest that brands can consider retaining e-wom into online marketing strategies to improve product purchase decisions. In addition, this study highlights the importance of considering country of origin when marketing products to consumers, as this can significantly influence product purchase decisions. This research contributes to the existing literature by providing insights into the role of e-wom, celebrity endorsers, and country of origin in product purchase decisions, and offers practical implications for brands.